Holograms in Education: Teachers’ Insights on the Future of Interactive Learning - Al-Modafar, Fouad Ahmed (Journal of Posthumanism, 2025)
This study delivers important findings about holographic technology integration for education, which fill a gap in research within Saudi Arabian schools.